2009
DOI: 10.1002/app.30138
|View full text |Cite
|
Sign up to set email alerts
|

Bulk free‐radical polymerization of styrene on a spinning disc reactor

Abstract: The bulk free-radical polymerization of styrene was carried out on a spinning disc reactor (SDR) with prepolymer feeds previously prepared in a stirred batch reactor at 70 C. The SDR significantly enhanced the reaction rate when the conversion of the prepolymer feed was about 50%. There was an optimal disc rotation speed, that is, 1500 rpm, at which the conversion enhancement was maximized. Increasing the disc rotation speed up to 1500 rpm increased the conversion, but a further increase beyond this speed caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Same Figure 4 demonstrates time savings of up to 50 min (depending on prepolymerized feed conversion) gained by a single pass on a SDR and evaluates utilization of nine passes on a SDR, whereby a time saving of 2 hours appears achievable. A multi-pass SDR study conducted by Moghbeli et al (2009) showed that considerable increases in conversion were indeed observed, but molecular weights and PDI slightly decreased, most probably due to chain scission of the long polymer chains subjected to the high shear forces. As previously mentioned, on the surface of the SDR thin, highly sheared films are formed, which are associated with high mixing intensities, high shear rates as well as plug flow characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Same Figure 4 demonstrates time savings of up to 50 min (depending on prepolymerized feed conversion) gained by a single pass on a SDR and evaluates utilization of nine passes on a SDR, whereby a time saving of 2 hours appears achievable. A multi-pass SDR study conducted by Moghbeli et al (2009) showed that considerable increases in conversion were indeed observed, but molecular weights and PDI slightly decreased, most probably due to chain scission of the long polymer chains subjected to the high shear forces. As previously mentioned, on the surface of the SDR thin, highly sheared films are formed, which are associated with high mixing intensities, high shear rates as well as plug flow characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Spinning disc reactors (SDRs) have received considerable attention as an intensified reactor technology which can produce highly sheared thin films with enhanced heat and mass transfer characteristics [1][2][3][4][5][6]. As a consequence the SDR has been shown to be suitable for exothermic reactions [7][8][9], and to be very effective as continuous-flow mixers which can offer important benefits over traditional batch processing equipment for intrinsically fast reactions [1].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics also encompasses dynamic fluidic thin films generated centrifugally by passing liquids over rotating surfaces, as in spinning disc processors (SDPs)3456789101112131415161718 and horizontally aligned rotating tube processors (RTPs) with open ends18192021222324. These processors are effective in controlling chemical reactions34567891011121322, probing the structure of self organised systems14, and exfoliation and scrolling of graphite and hexagonal boron nitride ( h -BN)318192021222324. However, the volumes of liquid required for maintaining constant shear intensity in the fluids flowing over the rotating surfaces, coupled with finite residence times and high cost of construction, can limit the scope of their applications.…”
mentioning
confidence: 99%
“…SDP has feed jets directed close to the centre of a rapidly rotating disc where there is intense micro-mixing, with residence times of typically less than a second, depending on the size of the disc, spinning speed, surface texture of the disc itself, viscosity of liquid and flow rates10. With respect to applications in organic synthesis, the SDP has been used to isomerize α-pinene7, control polymerization reactions368, and prepare 1,5-diketones as an entry to 2,4,6-triaryl pyridines9. Intriguingly, for the latter, several passes are required to move beyond the chalcone intermediate to form significant quantities of the desired 1,5-diketone9.…”
mentioning
confidence: 99%